Primordiality of Salvatore Scarpitta - Antonella Chiazza (Agathón)
The article analyzes the artistic research by Salvatore Scarpitta, one of the major protagonists of the international art scene after the Second World War, in its different phases: expressionist, abstract-figurative and informal. Through a historical-critical and aesthetic approach, proceeding onto reading some important works of art through an interpretative methodology, a further development of critical thinking by the artist's production.